Growing Live Disks within Cosmologically Assembling Asymmetric Halos: Washing Out the Halo Prolateness - Berentzen, Ingo; Shlosman, Isaac (The Astrophysical journal, 2006)
We study the growth of galactic disks in live triaxial dark matter (DM) halos. The halos have been assembled using the constrained realizations method and evolved from the linear regime using cosmological simulations. The "seed" disks have been inserted atredshift z = 3 and increased in mass tenfold over various time periods, 61-3 Gyr, with the halo responding quasi-adiabatically to this process. We follow the dynamical and secular evolution of the disk-halo system and analyze changes in the most important parameters, such as three-dimensional DM shapes, stellar (disk) and DM (halo) radial density profiles, and stellar bar development. We find that a growing disk is responsible for washing out the halo prolateness (in the disk plane) and for diluting its flatness over a period of time comparable to the disk growth. Moreover, we find that a disk that contributes more to the overall rotation curve in the system is also more efficient in axisymmetrizing the halo, without accelerating the halo figure rotation. The observational corollary is that the maximal disks probably reside in nearly axisymmetric halos, while disks whose rotation is dominated by the halo at all radii are expected to reside in more prolate halos. The halo shape is sensitive to the final disk mass, but is independent of how the seed disk is introduced into the system, abruptly or quasi-adiabatically. It is weakly sensitive to the timescale of the disk growth. We also expect that the massive disks are subject to a bar instability, while in light disks this instability is damped by the halo triaxiality. Implications of these results for the cosmological evolution of disks embedded in asymmetric halos are discussed and so are the corollaries for the observed fraction of stellar bars. Finally, the halo responds to the stellar bar by developing a gravitational wake--a "ghost" bar of its own, which is almost in phase with that in the disk.